Plotting to kill the president : assassination attempts from Washington to Hoover - Ayton, Mel (Potomac Books, an imprint of the University of Nebraska Press, 2017)
"Since the birth of our nation and the election of the first president, groups of organized plotters or individuals have been determined to assassinate the chief executive. From the Founding Fathers to the Great Depression, three presidents have been assassinated: Abraham Lincoln, James Garfield, and William McKinley. However, unknown to the general public, almost all presidents have been threatened, put in danger, or survived "near lethal approaches" during their terms. Plotting to Kill the President reveals the numerous, previously untold incidents when assassins, plotters, and individuals have threatened the lives of American presidents, from George Washington to Herbert Hoover. Mel Ayton has uncovered these episodes, including an attempt to assassinate President Hayes during his inauguration ceremony, an attempt to shoot Benjamin Harrison on the streets of Washington, an assassination attempt on President Roosevelt at the White House, and many other incidents that have never been reported or have been coveredup. Ayton also recounts the stories of Secret Service agents and bodyguards from each administration who put their lives in danger to protect the commander in chief. Plotting to Kill the President demonstrates the unsettling truth that even while the nation sleeps, those who would kill the president are often hard at work devising new schemes."--